2021
DOI: 10.1128/iai.00105-21
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Microbial Signatures Are Predictive of the Risk of Fungal Pneumonia in Hematologic Patients

Abstract: The ability to predict invasive fungal infections (IFI) in patients with hematological malignancies is fundamental for successful therapy. Although gut dysbiosis is known to occur in hematological patients, whether airways dysbiosis also contributes to the risk of IFI has not been investigated. Nasal and oropharyngeal swabs were collected for functional microbiota characterization in 173 patients with hematological malignancies recruited in a multicenter, prospective, observational study and stratified accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
4
12
0
Order By: Relevance
“…As the dysbiotic expansion of Enterobacteriacae is associated with a worse outcome in children with CF [ 30 , 31 ], and contributes to infectious pathology in the lung [ 32 ], preliminary as they are, these data indicate a specific 3-IAld-dependent regulation of local microbial composition that could be of benefit in CF. Moreover, the expansion of L. reuteri , known to provide epithelia barrier function at mucosal surfaces [ 33 ], points to the unique ability of 3-IAld to dually act at the microbe/host interface.…”
Section: Resultsmentioning
confidence: 99%
“…As the dysbiotic expansion of Enterobacteriacae is associated with a worse outcome in children with CF [ 30 , 31 ], and contributes to infectious pathology in the lung [ 32 ], preliminary as they are, these data indicate a specific 3-IAld-dependent regulation of local microbial composition that could be of benefit in CF. Moreover, the expansion of L. reuteri , known to provide epithelia barrier function at mucosal surfaces [ 33 ], points to the unique ability of 3-IAld to dually act at the microbe/host interface.…”
Section: Resultsmentioning
confidence: 99%
“…It has been noted that the microbiome may also be involved in protection against Aspergillus [15,16]. In this regard, we have recently shown that the composition of the oropharyngeal microbiome could predict the risk of fungal pneumonia in hematological patients [17]. In particular, an increased risk of fungal pneumonia was associated with the loss of protective anaerobes such as Clostridiales and Bacteroidota and the expansion of pathogenic Proteobacteria, as confirmed in a murine model of aspergillosis [17].…”
Section: Introductionmentioning
confidence: 66%
“…We have previously shown that strictly anaerobic bacteria, such as Prevotella oris and Peptostreptococcus anaerobius, representative members of Bacteroidota and Firmicutes (order Clostridiales), respectively, protected against infection in a murine model of aspergillosis [17]. Since anaerobic bacteria produce SCFAs, we evaluated the presence of butyric acid and isobutyric acid in in vitro cultures and found that Prevotella oris and Peptostreptococcus anaerobius produced the two SCFAs both in the presence and in the absence of Aspergillus (Figure 1).…”
Section: Aspergillus Infection Is Associated With the Production Of Scfasmentioning
confidence: 99%
See 2 more Smart Citations